Metal–Organic Framework-Based Materials for Energy Conversion and Storage - Qiu, Tianjie; Liang, Zibin; Guo, Wenhan; Tabassum, Hassina; Gao, Song; Zou, Ruqiang (ACS energy letters, 2020)
Metal–organic frameworks (MOFs) have emerged as desirable cross-functional platforms for electrochemical and photochemical energy conversion and storage (ECS) systems owing to their highly ordered and tunable compositions and structures. In this Review, we present engineering principles promoting the electro-/photochemical performance of MOF-based materials for ECS by component design and nanostructuring. Through the discussion of the engineering strategies of pristine MOFs, MOF composites, and their derivatives for ECS, the superiority and composition–structure–activity relationships of the engineered MOF-based materials with advanced components and nanostructures will be clarified. Finally, we provide a concluding discussion on the challenges and direction of future development in this emerging area of MOF-based materials for ECS.